EPEN-08. A SPATIAL AND PROGNOSTIC ANALYSIS OF IMMUNE CELL INFILTRATE IN PAEDIATRIC EPENDYMOMA. Issue 2 (22nd June 2018) - Ritzmann, Timothy A; Francis, Francesca; Brudenell, Sarah-Louise; Rogers, Hazel A; Virasami, Alex; Jacques, Thomas S; Paine, Simon ML; Grundy, Richard G
Abstract: Ependymoma is the second most common malignant brain tumour of childhood. The immune environment has been implicated in recurrence, but more research is needed to understand its role. We performed immunohistochemistry on tumour sections for the T-cell markers CD4 and CD8, B-cell marker CD20 and inflammatory markers CD45 and CD68. 55 paired primary and first recurrent tumours plus 19 non-recurrent tumours were included. Baseline clinical and DNA methylation characteristics were representative of other paediatric ependymoma cohorts. Levels of CD4, CD8 and CD20 were low within the tumour parenchyma but higher for CD45 and CD68. All markers, other than CD68, were more highly expressed in non-parenchymal than parenchymal areas (p<0.001). Higher levels were also seen in perivascular regions. There was a significant fall in CD45 cells at first recurrence compared to primary (p=0.009) and this appeared to be restricted to posterior fossa tumours. There was no difference at relapse for other markers. Higher CD45 and CD68 expression was associated with tumours that relapsed (p=0.019 and p<0.001). Infiltration with CD20+ and CD8+ cells at primary diagnosis were associated with poorer survival for patients who recurred (p=0.007, p=0.009). The spatial distribution of infiltrating immune cells supports a hypothesis that paediatric ependymoma is a T-cell excluded tumour. The fall in inflammatory (CD45) infiltrate at recurrence indicates a possible immune subversion process. Mechanisms of immune cell exclusion from the tumour parenchyma need to be better characterised in order to understand the implications for immunotherapy. The association between recurrence and inflammatory infiltrate needs further investigation.